2022
DOI: 10.1038/s41588-022-01252-3
|View full text |Cite
|
Sign up to set email alerts
|

Spurious transcription causing innate immune responses is prevented by 5-hydroxymethylcytosine

Abstract: Generation of functional transcripts requires transcriptional initiation at regular start sites, avoiding production of aberrant and potentially hazardous aberrant RNAs. The mechanisms maintaining transcriptional fidelity and the impact of spurious transcripts on cellular physiology and organ function have not been fully elucidated. Here we show that TET3, which successively oxidizes 5-methylcytosine to 5-hydroxymethylcytosine (5hmC) and other derivatives, prevents aberrant intragenic entry of RNA polymerase I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…In addition to 5hmC deposition at enhancers, the significance of the accumulation of these marks within gene bodies (and in particular its positive correlation with gene transcription) is now being investigated. Very recent evidence suggests that the intragenic generation of 5hmC by TET3, specifically, may act to stabilize full-length gene transcripts by preventing aberrant Pol II-dependent initiations within gene bodies [ 56 ]. It is also noteworthy that most of the TET3-dependent 5hmC marks, observed within the EndoG locus were at CpA, rather than at CpG, dinucleotides.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to 5hmC deposition at enhancers, the significance of the accumulation of these marks within gene bodies (and in particular its positive correlation with gene transcription) is now being investigated. Very recent evidence suggests that the intragenic generation of 5hmC by TET3, specifically, may act to stabilize full-length gene transcripts by preventing aberrant Pol II-dependent initiations within gene bodies [ 56 ]. It is also noteworthy that most of the TET3-dependent 5hmC marks, observed within the EndoG locus were at CpA, rather than at CpG, dinucleotides.…”
Section: Discussionmentioning
confidence: 99%
“…However, these changes are usually less than the strong differences in DNA methylation that are tissue specific. Another caveat is that WGBS does not distinguish between genomic 5-methylcytosine (5mC) and 5-hydroxymethylcytosine (5hmC), which often have different biological effects [62,63]. This is not a complication for Myob-hyperm DMRs because we found that myoblast cell strains have little or no 5hmC at tested CpG sites in 13 examined myoblast RRBS-delineated DMRs, including one in the CDH15 intragenic Myob-hyperm DMR overlapping a cryptic intragenic promoter [13].…”
Section: Discussionmentioning
confidence: 88%
“…However, CpG content within the coding regions of certain genes is high. Intragenic methylation has been shown to protect gene bodies from aberrant entry of RNA polymerase II, which can lead to spurious expression 57,58 . We show that >16,000 4d sites that form CpGs are under high constraint in mammals.…”
Section: Discussionmentioning
confidence: 99%